Identification Of Objects By Machines Using RFID Technology Identify objetcs in Internet of Things - Salim, Douae; Setti, Larbi; Elabderrahm, Abdellatif (Transactions on Engineering and Computing Sciences, 2017)
Embedded Systems and Internet of Things know recently a revolution in terms of innovation. With connectivity and networks, embedded systems are becoming more communicative, intelligent, and autonomous. They had the ability to calculate, process information, and perception. Digital connectivity to physical objects requires, firstly, the identification of objects, in order to be able to recognize each object in a unique way and to collect the data stored, ensuring security and confidentiality. In this paper we will examine the RFID technology (Radio-frequency Identification), which enables wireless interaction over certain frequency of RFID readers with a network system, to uniquely identify, track and capture informations at varying distances without the need of human interaction. Typically, RFID readers, which emits electromagnetic waves at a certain power, in order to activate the RFID tags, if it presents in the reader’s transmission range. RFID tags respond to the reader’s request by emitting radio waves back with the data stored the chip. Furthermore, we will explore Identification algorithm and communication techniques between reader and tags to avoid collision, whenever a large volume of tags must be read together, or perform a transmission in the same RF field at the same time. In addition, we will describe communications protocol between reader and the information system.